1990
DOI: 10.1007/bf01959396
|View full text |Cite
|
Sign up to set email alerts
|

Brittle cornea syndrome: An heritable connective tissue disorder distinct from Ehlers-Danlos syndrome type VI and fragilitas oculi, with spontaneous perforations of the eye, blue sclerae, red hair, and normal collagen lysyl hydroxylation

Abstract: We report a patient with the characteristic features of the brittle cornea syndrome, a rare, autosomal recessively inherited disorder, namely brittle corneae, blue sclerae, and red hair. The patient also showed joint hyperextensibility, a soft skin, and dysplastic auricles with unusually soft cartilage. Phenotypically, the disorder bears a certain resemblance to fragilitas oculi and the type VI (ocular) form of the Ehlers-Danlos syndrome, two conditions which are, themselves, not readily distinguishable. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
0
20
1
1
Order By: Relevance
“…5 Light microscopy of skin biopsies did not reveal any gross abnormalities of the architecture of the skin. We did not observe the "holes" in the dermis reported by Royce et al 8 Transmission electron microscopy revealed collagen fibrils in IV-4 to have a normal diameter. In IV-6, we observed minor variation in the diameter of the fibrils, and slightly thinner fibrils could be seen in some areas (data not shown).…”
Section: Morphologic Studiescontrasting
confidence: 38%
See 1 more Smart Citation
“…5 Light microscopy of skin biopsies did not reveal any gross abnormalities of the architecture of the skin. We did not observe the "holes" in the dermis reported by Royce et al 8 Transmission electron microscopy revealed collagen fibrils in IV-4 to have a normal diameter. In IV-6, we observed minor variation in the diameter of the fibrils, and slightly thinner fibrils could be seen in some areas (data not shown).…”
Section: Morphologic Studiescontrasting
confidence: 38%
“…In one report, 40-to 60-m holes were described in the dermis. 8 Other investigators have observed minor variation in collagen fibril diameter, 18 as seen in IV-6. In general, however, the morphology of the skin has been rather unremarkable with respect to both the gross architecture and the structure of the collagen fibrils.…”
Section: Discussionmentioning
confidence: 95%
“…These cells were homogenized in the extraction buffer and the supernatants were used for determining the enzyme activity as previously reported (Royce et al, 1990). Recombinant baculoviruses (Ac3A1) containing human type III procollagen cDNA were prepared as reported previously (Tomita et al, 1995).…”
Section: Determination Of Prolyl 4-hydroxylase Activitymentioning
confidence: 99%
“…The congenital form can be part of Ehlers-Danlos syndrome type Vl, or part of the corneal syndrome associated with blue sclera and red hair (Royce et al, 1990).…”
Section: Keratoglobusmentioning
confidence: 99%